Roger Ebert's four-star reviews, 1967-2007 - Ebert, Roger (Andrews McMeel Publishing, LLC, 2007)
Presents a collection of the critic's most positive film reviews of the last four decades, arranged alphabetically from "About Last Night" to "Zodiac."